Analysis Magnetic Mineral Content of Natural Iron Sand in Beach Island Lombok as Basic Materials of Micro Wave Absorbers - Suslawati Susilawati; Aris Doyan; Saprizal Hadisaputra (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to analyze the content of the magnetic mineral compound of natural iron sand on the beach of Lombok Island. This study uses the experimental method by taking primary data which is carried out in three locations, namely at Ijobalit Beach (East Lombok), Cemara Beach (West Lombok), and Telindung Beach (East Lombok). The study stage begins with a separation of natural iron sand, then a magnetic mineral separation is carried out to obtain Fe3O4 powder. The last stage is testing the Fe content using AAS (atomic absorption spectrophotometry). The research results were obtained by the percentage of magnetic mineral content from Ijobalit beach sand, Cemara Beach, and Telindung Beach respectively 93.56, 72.99, and 87.00%. The results showed that natural iron sand from Ijobalit beach had great potential to be used as a basic material for making microwave absorbers.